Fiscal Policy Formulation and Implementation in Oil-Producing Countries - Davis, Jeffrey (International Monetary Fund, 2003)
Countries with large oil resources can benefit substantially from them. However, despite their huge natural resources, many oil producers have had disappointing growth, widespread poverty, and continuing vulnerability to oil price and other external shocks. Fiscal policy can play a central role indetermining the extent to which a country benefits from its oil wealth. This book brings together studies that provide analysis and findings on fiscal policy issues in oil-producing countries from a diverse international perspective. A key focus for the authors is how to manage oil resources in a way that contributes to a stable macroeconomic environment, sustainable growth, and poverty reduction.